An evidence-based quality improvement perspective for a chronic obstructive pulmonary disease case-finding program. (August 2014) - Estes, Tracy S; Short, Nancy; Bowser, Donna; Boyle, Anne
Chronic obstructive pulmonary disease (COPD) is a persistent progressive respiratory disease that is increasing in prevalence and cost in the United States health care system. Delays in recognition, diagnosis, and treatment are associated with poorer clinical outcomes. These delays are seen more often in populations experiencing economic hardship, lack of access to care, and lack of insurance, such as those seen in an indigent care clinic. The COPD case-finding program was planned as an evidence-based quality improvement project with a prospective, descriptive design generating a convenience sample of patients meeting modified screening criteria (i.e. patients 40 years of age with a smoking history and no pulmonary disease history) in a community-based indigent care clinic which was not screening for COPD. Practice change recommendations were guided by the Diffusion of Innovations Model. Descriptive statistics were used to describe the sample (i.e. age, ethnicity, race, gender, income, and selected comorbidities). Sensitivity, specificity, positive predictive value, negative predictive value, prevalence, and receiver operator characteristics curve COPD Questionnaire were calculated for this sample.